Pengembangan Model Pembelajaran Pendidikan Jasmani Berbasis Kinestetik untuk Meningkatkan Kebugaran Jasmani Siswa Sekolah Dasar - Wiji Astuti (Jurnal Simki Postgraduate, 2023)
The purpose of this research is to: 1) Develop a physical education learning model that can be used to improve physical fitness in elementary school children; 2) Making packaging for a physical education learning model that can be used as a teaching guide for elementary school-age children in CD form and equipped with implementation instructions so that the teacher can easily understand and implement it. This development research was carried out with an educational research and development (R & D) research design using the Instructional Development Model approach. The small-scale trial was conducted on 19 students at SDN Ngasem, Kediri Regency, while the large-scale trial was carried out on students at SDN Ngasem, SDN Nglumbang, SDN Blimbing, SDN Bogem, and SDN Bangkok 2, Kediri Regency, all of which totaled 111 student. The data collection instruments used were: 1) interview guidelines, 2) value scales, 3) observation guidelines for learning models, 4) acceptability, and 5) observation guidelines for educators conducting trials. The data analysis technique used is quantitative descriptive analysis and qualitative analysis. The results of this study are in the form of a kinesthetic-based physical education learning model which is documented on a CD and a guidebook for implementing learning in class III elementary school students. The learning model is divided into 9 posts, namely: 1) walking and jumping on the catwalks, 2) jumping the goal, 3) moving the colored cubes, 4) throwing the ball towards the target, 5) kicking the ball into the goal, 6) rolling forward , 7) crawling in the tunnel, 8) crawling under the spider rope, and 9) climbing the rope. All items in the post are packaged in the form of a series of activities. At the end of this study it can be concluded that the learning model that is made is very interesting, in accordance with the characteristics of students, can be used as a way of teaching physical education and is very effective for developing multiple intelligences.